Implikasi Ketegangan Houthi–Israel terhadap Stabilitas Jalur Perdagangan di Negara Pesisir Laut Merah 2023-2024 - Abellia Noricha Ananta silalahi; Elita Nurdea; Tiara Ananda; Kevin Kristiandi (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2026)
This study examines the implications of tensions between the Houthi group and Israel on the stability of trade routes in Red Sea coastal states during 2023–2024. The conflict, which began with Houthi solidarity with Palestine, escalated into attacks on commercial vessels in the Red Sea and Gulf of Aden, disrupting freedom of navigation and transforming strategic trade corridors into high-risk zones. Using Keitaro Ushirogata's maritime security theory and a qualitative case study approach, this research analyzes three main aspects: area denial as a Houthi strategy, sea control through coastal state cooperation, and power projection by the United States through Operation Prosperity Guardian. The findings indicate that this tension impacts not only maritime security but also global economic stability and inequality in world trade governance. Coastal states such as Egypt, Yemen, and Djibouti have suffered economic losses due to declining port activities and rising logistics costs. This study concludes that regional conflicts involving non-state actors can disrupt the global trading system. Therefore, fairer and more inclusive international maritime cooperation is needed to maintain the security and smooth flow of strategic trade routes in the Red Sea.